2014
DOI: 10.1111/hiv.12162
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of cardiovascular disease (CVD) with age in HIV‐positive men: a comparison of the D:A:D CVD risk equation and general population CVD risk equations

Abstract: ObjectivesThe aim of the study was to statistically model the relative increased risk of cardiovascular disease (CVD) per year older in Data collection on Adverse events of anti-HIV Drugs (D:A:D) and to compare this with the relative increased risk of CVD per year older in general population risk equations. MethodsWe analysed three endpoints: myocardial infarction (MI), coronary heart disease (CHD: MI or invasive coronary procedure) and CVD (CHD or stroke). We fitted a number of parametric age effects, adjusti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 27 publications
(61 reference statements)
3
24
0
Order By: Relevance
“…Freiberg et al looked at the veteran population and found an increase rate of cardiovascular events in HIV-infected male veterans compared with HIV-uninfected male veterans HR 1.48 (95% CI, 1.27-1.72) [3]. Similarly, Silverberg et al demonstrated a 44% increased risk of MIs among a predominately male HIV-infected population compared with a predominately male HIV-uninfected population [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Freiberg et al looked at the veteran population and found an increase rate of cardiovascular events in HIV-infected male veterans compared with HIV-uninfected male veterans HR 1.48 (95% CI, 1.27-1.72) [3]. Similarly, Silverberg et al demonstrated a 44% increased risk of MIs among a predominately male HIV-infected population compared with a predominately male HIV-uninfected population [48].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies report increased risk of CHD in HIV-infected people, but most of these studies were conducted in men or in predominantly male cohorts [3][4][5]. In the general population, men have been reported to have higher rates of CHD and at younger age than women [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the people who didn't take much care of their health when they were younger, in the 20's, would develop much of the related risk conditions as they entered the middle age. A number of studies reported that CVD prevalence increases with the increasing age (Al-Alwan et al, 2013;Petoumenos et al, 2014;Peker et al, 2002). Another study reported that, with increasing age there was a gradual shift for DBP to SBP as a predictor of CHD risk (Franklin et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…While aspirin has not been evaluated for cancer prevention in people with HIV, it has been studied in this population for modulation of cardiovascular risk. HIV patients have a higher risk of cardiovascular disease than the general population 221,222 . In addition to traditional cardiovascular risk factors, low CD4+ counts and increased inflammation are biomarkers of risk in people with HIV.…”
Section: Cancer Prevention Interventionsmentioning
confidence: 99%